Natural variation of Macrocystis pyrifera gametophyte germplasm culture microbiomes and applications for improving yield in offshore farms - Osborne, Melisa G (Journal of phycology, 2023)
© 2023 The Authors. Journal of Phycology published by Wiley Periodicals LLC on behalf of Phycological Society of America.